PENGARUH LEVERAGE, PROFITABILITAS DAN PUBLIC SHARE TERHADAP KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN PERUSAHAAN PADA PERUSAHAAN INDUSTRI OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008 – 2012 - Irham -; Taufeni Taufik; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The data used is secondary data obtained through the Indonesian Capital Market Directory (ICMD). Data analysis methods used to perform hypothesis testing is multiple regression analysis. Before testing the hypothesis, first proposed regression equations were tested for normality of data and assumptions to be free from bias classic. These results indicate that Leverage as measured by debt-to-equity ratio (DER) affect the completeness of the disclosure of financial statements. Profitability as measured by Return on Assets (ROA) affect the completeness of the disclosure of financial statements. Public Share affect the completeness of the disclosure of financial statements. Simultaneously, DER, ROA and Public Share affect the completeness of the disclosure of financial statements. The coefficient of determination is 0.372 which shows the influence of the independent variables used in the model study of smoothing earnings as the dependent variable was 37.2%, while the rest (62.8%) is explained by other variables not included in this research mode.Keywords: Leverage, Profitability, Public Share, and Fittings Company Financial Statements